2013
DOI: 10.1038/nsmb.2600
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for diverse N-glycan recognition by HIV-1–neutralizing V1–V2–directed antibody PG16

Abstract: HIV-1 uses a diverse N-linked-glycan shield to evade recognition by antibody. Select human antibodies, such as the clonally related PG9 and PG16, recognize glycopeptide epitopes in the HIV-1 V1–V2 region and penetrate this shield, but their ability to accommodate diverse glycans is unclear. Here we report the structure of antibody PG16 bound to a scaffolded V1–V2, showing an epitope comprising both high mannose–type and complex-type N-linked glycans. We combined structure, NMR and mutagenesis analyses to chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
319
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(342 citation statements)
references
References 61 publications
16
319
2
Order By: Relevance
“…A triad of aspartic acid residues provides a highly anionic potential to the tip of the PGDM1400 CDRH3 (Fig. 3C), which likely interacts with cationic residues in the gp120 V1/V2, as seen for PG9 and PG16 (29,30). The 2D-class averages of the PGDM1400 Fab-BG505 SOSIP gp140 trimer complex obtained by single-particle negative-stain electron microscopy revealed that only a single Fab is bound at the trimer apex and binds predominantly along the threefold axis, in contrast to the shallower binding angle described for PG9 (Fig.…”
Section: Somatic Variant Pgdm1400 Is Broader and More Potent Thanmentioning
confidence: 98%
“…A triad of aspartic acid residues provides a highly anionic potential to the tip of the PGDM1400 CDRH3 (Fig. 3C), which likely interacts with cationic residues in the gp120 V1/V2, as seen for PG9 and PG16 (29,30). The 2D-class averages of the PGDM1400 Fab-BG505 SOSIP gp140 trimer complex obtained by single-particle negative-stain electron microscopy revealed that only a single Fab is bound at the trimer apex and binds predominantly along the threefold axis, in contrast to the shallower binding angle described for PG9 (Fig.…”
Section: Somatic Variant Pgdm1400 Is Broader and More Potent Thanmentioning
confidence: 98%
“…Man 5 GlcNac 2 (52). V1V2 bnAb interactions with various glycans and direct strand-strand contact between the extended CDR H3 and the C strand of the V1V2 domain are common traits among individual V1V2 bnAbs (51, 52, 55, 56). For immunogen design, despite V1V2 glycan bnAb preference for binding to a quaternary epitope, PG9, PG16 and CH01 bnAbs, as well as the CH01 lineage unmutated common ancestor (UCA), can also bind a minor subset of monomeric gp120 Envs (15, 57) and minimal Env forms (58).…”
Section: Characteristics Of Broadly Neutralizing Antibodiesmentioning
confidence: 99%
“…2F5 and 4E10 are directed against the HIV-1 gp41 membrane-proximal external region (MPER). 53,54 IgG1b12 (b12) and VRC-CH31 are directed against the HIV-1 gp120 CD4-binding site 55,56 ; CH01, PG9, and PG16 are directed against the HIV-1 gp120 V1-V2 conformational epitope [56][57][58][59] ; and 2G12 is directed against a distinct HIV-1 gp120 epitope. 60 …”
Section: A3r5/env-imc-lucr Neutralization Assaymentioning
confidence: 99%